PERBEDAAN PENGETAHUAN TENTANG KARIES GIGI PADAANAK SEKOLAH DASAR GMIM 20 (kelas 4-5 ) DAN YAYASAN Ds.A.Z.R.WENAS SEKOLAH DASAR GMIM MALALAYANG ( kelas 4-5 ) KOTA MANADO - Ni Made Yuliana; Jeineke E. Ratuela; Yenny Lisbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Knowledge is the result of knowing one's object through the senses it has (eyes, nose, ears, and so on). Most of a person's knowledge is obtained through the sense of hearing (ears), and the sense of sight (eyes). A person's knowledge of objects has different intensities or levels. The purpose of this study was to determine the differences in knowledge of dental caries in elementary school students GMIM 20 (grades 4-5) and the Ds.A.Z.R Foundation. Wenas Elementary School GMIM Malalayang Manado City. This type of research uses an analytical survey research method that is a comparative study with a cross sectional approach. The sample used is 89 respondents. Consisting of 46 respondents at GMIM 20 Elementary School and 43 respondents at Ds.A.Z.R. Elementary School. Wenas. This research instrument uses a questionnaire containing questions. The data obtained were tabulated and presented in the form of a frequency distribution table and analysis test using independent t-test.From the test results using the independent t-test that the p value of sig. (2-tailed) = 0.000 < = 0.05 indicates that there is a significant difference, thus H0 is accepted H1 is rejected so that it can be concluded that there is a difference in the knowledge of grade 4 and 5 students between GMIM 20 Elementary School and Ds.A.Z.R. Foundation Elementary School. Wenas city of Manado.